รูปแบบความเป็นองค์กรนวัตกรรมเพื่อการพัฒนาทรัพยากรมนุษย์ของธนาคารพาณิชย์ไทย - แสงมณีเดช, ถิรวุฒิ (Academic Journal Phranakhon Rajabhat University, 2017)
The purposes of this research were to 1) study the condition of the innovative organization for human resource development of Thai commercial banks, and 2) develop and examine the consistency of confirmatory factor analysis model of casual factors influencing the innovative organization for human resource development of Thai commercial banks. The quantitative and qualitative research methodology. The results of this research revealed that 1) the condition of the innovative organization for human resource development of Thai commercial banks emphasizes on the human resource development as the important human capital of the organization. Thai commercial banks consequently contain the human resource development plan in the vision of organization. Thai commercial banks have the basic beliefs that the capability of the efficient human resource management can be developed by the process of proficiency development. 2) The model of the innovative organization for human resource development of Thai commercial banks, called “KOCI Model”, consists of vision, mission, and goal. The elements of the innovative organization consist of 1) K = Knowledge Management, 2) O = Organizational Learning, 3) C = Cultural Learning, and 4) I = Innovative Organization. All elements are statistically significant at the .05 level and have the measure reliability in high level. The result of the model consistency examination revealed that model suits to the empirical data. (c2= 121.79, p = 0.06844, GFI= 0.96, AGFI = 0.95, RMSEA = 0.02, CN = 437.38)